Bayesian analysis of the growth of pears in the cultivate Shinseiki using non-linear models - Rodrigues, Gabriela; Villegas, Cristian; Savian, Taciana (Brazilian Journal of Biometrics, 2024)
The pear of the Pyrus genus is the third most consumed fruit in Brazil, however, internal production is low and most demand is obtained through imports. Brazil has favorable conditions for its cultivation and one of its main economic sectors is agriculture, being responsible for generating a large number of jobs and income for the country. In this sense, studies related to this fruit can provide information and encourage its production. Using non-linear models, it is possible to identify growth patterns such as fruit length and diameter, which can help determine the ideal harvest point. Therefore, the goal of this article was to compare the Logistic and Gompertz non-linear models in describing the growth curves in diameter and length of the Asian pear tree using the Bayesian approach. The results indicated the Logistic model as the best to describe these two variables and provided asymptotic averages of 70.0607 and 79.706 for length and diameter, respectively.